« Musulman », une catégorie révolutionnaire: Perspectives de parents au sein de la prévention des radicalisations violentes en Suisse = "Muslim", a Revolutionary Category: Parent’s Perspectives on Preventing Violent Radicalization in Switzerland - Siggen, Anne (Social sciences and missions, 2025)
The article analyzes how parents who use a structure for the prevention of violent radicalization in Switzerland experience and manage their child’s conversion to Islam. Based on ethnography and interviews, the study shows how conversion triggers misunderstanding, fear and a feeling of powerlessness in parents in the face of a new religious identity perceived as subversive. The analysis is based on the concept of the "revolutionary category", illustrating how conversion redefines parent-child relationships. The institution plays a regulatory role with parents by offering specialized support to help them better understand the changes they are experiencing., AbstractThe article analyzes how parents who use a structure for the prevention of violent radicalization in Switzerland experience and manage their child’s conversion to Islam. Based on ethnography and interviews, the study shows how conversion triggers misunderstanding, fear and a feeling of powerlessness in parents in the face of a new religious identity perceived as subversive. The analysis is based on the concept of the "revolutionary category", illustrating how conversion redefines parent-child relationships. The institution plays a regulatory role with parents by offering specialized support to help them better understand the changes they are experiencing.